Pharmacokinetics and tissue distribution of four major bioactive components of Cynanchum auriculatum extract: a UPLC–MS/MS study in normal and functional dyspepsia rats - Sun, Jia; Meng, Xin; Huang, Di; Gong, Zipeng; Liu, Chunhua; Liu, Ting; Pan, Jie; Lu, Yuan; Zheng, Lin (Frontiers in Pharmacology, 2023)
Cynanchum auriculatum (CA) is usually used to treat digestive disorders, such as anorexia, enteritis, dysentery, and indigestion. Functional dyspepsia (FD) is characterized by a group of symptoms associated with the gastroduodenal region. Recent pharmacological studies have demonstrated the efficacy of CA for treating FD. However, the pharmacokinetics (PK) and tissue distribution of CA in physiological and FD states is still unclear. The present study aimed to clarify the differences in PK parameters and tissue distribution of the four major active components of CA (baishouwu benzophenone, deacylmetaplexigenin, qingyangshengenin, and syringic acid) under both physiological and FD states. For this, normal and FD rats were orally administered 10 mg/kg CA extract. Then, plasma and tissue (heart, liver, spleen, lung, kidney, brain, stomach, and small intestine) samples were obtained. The four active components of CA in rat plasma and tissues were quantified by developing and validating a fast and reliable ultra-high-performance liquid chromatographymass spectrometry method. The area under the plasma concentration-time curve from time zero to time t (AUC 0-t ) of baishouwu benzophenone was significantly lower in the FD group than in the normal group (P<0.01). The FD group had significantly lower (P<0.001) apparent volume of distribution and plasma clearance of qingyangshengenin and significantly higher (P<0.05) AUC 0-t of deacylmetaplexigenin and qingyangshengenin. The four active components were rapidly distributed into various tissues, and the main target organs of CA activity were the stomach and small intestine. In addition, baishouwu benzophenone, deacylmetaplexigenin, and qingyangshengenin could cross the blood-brain barrier, indicating that the brain may be another target organ in the treatment of FD. These results indicate that the pathological state of FD alters the PK behavior and tissue distribution This is a provisional file, not the final typeset article characteristics of baishouwu benzophenone, deacylmetaplexigenin, qingyangshengenin, and syringic acid in the CA extract, providing an experimental basis for the role of CA in FD treatment.